Shaping romance : interpretation, truth, and closure in twelfth-century French fictions - Bruckner, Matilda Tomaryn (Philadelphia : University of Pennsylvania Press, 1993)
Examines a set of five twelfth-century romance texts--complete and fragmentary, canonical and now neglected, long and short--to map out the characteristics and boundaries of the genre in its formative period.
Marie's Textual Identity: Names and TitlesMarie's Fusion of Voices -- Orality and Writing, Orality in Writing -- Closing and Opening the Collection -- Conclusion -- Notes -- Bibliography of Works Cited -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z
Print version record.
Includes bibliographical references (pages 267-284) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Tristan -- (Legendary character) -- Romances -- History and criticism; Tristan -- (Legendary character); French poetry -- To 1500 -- History and criticism; Narrative poetry, French -- History and criticism; Arthurian romances -- History and criticism; Knights and knighthood in literature; Romances -- History and criticism; Fictions, Theory of; Rhetoric, Medieval; Closure (Rhetoric); Poésie française -- Jusqu'à 1500 -- Histoire et critique; Cycle d'Arthur -- Histoire et critique; Roman courtois -- Histoire et critique; Théorie de la fiction; Rhétorique médiévale.; Conclusion (Littérature); Poésie narrative française -- Histoire et critique; POETRY -- Continental European; LITERARY CRITICISM -- Medieval; Arthurian romances; Closure (Rhetoric); Fictions, Theory of; French poetry; Knights and knighthood in literature; Narrative poetry, French; Rhetoric, Medieval; Romances; Middeleeuwse romans (teksten); Frans; To 1500; Criticism, interpretation, etc